Complete genome sequence of enterococcus faecalis strain SGAir0397, isolated from a tropical air sample collected in Singapore - Purbojati, Rikky Wenang (2020)
Enterococcus faecalis strain SGAir0397 was isolated from a tropical air sample collected in Singapore. Its genome was assembled using single-molecule real-time sequencing data and comprises one circular chromosome with a length of 2.69 Mbp. The genome contains 2,595 protein-coding genes, 59 tRNAs, and 12 rRNAs.